2004
DOI: 10.1111/j.1600-0447.2004.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypofrontality in schizophrenia: a meta‐analysis of functional imaging studies

Abstract: Meta-analysis supports resting hypofrontality in schizophrenia. Task-activated hypofrontality is also supported, but there is little from voxel-based studies to suggest that this is associated with an altered pattern of regional functional architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
162
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 293 publications
(180 citation statements)
references
References 128 publications
(204 reference statements)
12
162
2
3
Order By: Relevance
“…We have recently demonstrated involvement of dopamine D 1 receptors (McLean et al 2009a) while others have shown serotonin 5-HT 1A receptor involvement (Nagai et al 2009) in mechanisms for improvement of PCP-induced deficits in this task. This work combined with recent results from a preliminary study using female Long Evans rats suggests that the sub-chronic PCP treated rats have reduced prefrontal cortical dopamine activation in this task providing considerable support for this as a model of cognition in schizophrenia, as hypofrontality is a key feature of schizophrenia pathology (Hill et al 2004). In our study, sub-chronic vehicle treated rats showed significantly increased prefrontal cortical dopamine levels during the retention phase of the task only, as measured by in vivo microdialysis.…”
Section: Novel Object Recognitionmentioning
confidence: 60%
“…We have recently demonstrated involvement of dopamine D 1 receptors (McLean et al 2009a) while others have shown serotonin 5-HT 1A receptor involvement (Nagai et al 2009) in mechanisms for improvement of PCP-induced deficits in this task. This work combined with recent results from a preliminary study using female Long Evans rats suggests that the sub-chronic PCP treated rats have reduced prefrontal cortical dopamine activation in this task providing considerable support for this as a model of cognition in schizophrenia, as hypofrontality is a key feature of schizophrenia pathology (Hill et al 2004). In our study, sub-chronic vehicle treated rats showed significantly increased prefrontal cortical dopamine levels during the retention phase of the task only, as measured by in vivo microdialysis.…”
Section: Novel Object Recognitionmentioning
confidence: 60%
“…In addition many studies, in both humans (Langsjo et al, 2004;Vollenweider et al, 1997aVollenweider et al, , 1997b and animals (Chih-Liang et al, 2011;Dawson et al, 2013), have been dedicated to elucidate the impact of acute, subanesthetic ketamine treatment on regional brain functioning, with PFC hypermetabolism (hyperfrontality) most consistently reported. The paradox of this ketamine-induced hyperfrontality given the hypofrontality characteristic of long-term schizophrenia (Hill et al, 2004) has not been resolved. Surprisingly, despite the widespread use of ketamine treatment as a translational model there is a relative paucity of data on how acute ketamine treatment impacts on the functional interactions between brain regions and the neural subsystems known to be dysfunctional in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of the purported relationships between task performance and the frontal lobes requires further examination in schizophrenia using imaging techniques. However, a meta-analytic review of imaging studies has confirmed the presence of ' hypofrontality ' in schizophrenia patients, both for resting and cognitive challenge studies (see Hill et al 2004).…”
Section: Introductionmentioning
confidence: 99%